The correlation between training with weights and plyometric training, and their impact on the development of certain physical qualities in shooting in extension for handball players - Djamel, M.; Houcine, B.; Mohamed, K. S.; Habib, B. (The Russian Journal of Physical Education and Sport, 2017)
Strength training is the basis for the physical preparation of players of different age groups. Many researchers highlight the need for weight training in the content of training programs. The aim of this research is to understand the correlation between weight training and plyometric training and their impact on the development of certain physical qualities and the extension shooting for handball players (13-15 years) through a proposed training program for identification of the following: Effect of training with weights and plyometric training and their impact on the development of certain physical qualities and shooting in extension for Handball players. Materials.The research sample consisted of 64 cadet players, practicing in four different teams in the Hand Ball regional championship, in the west, divided into four groups of 16 players. The researchers carried out an experimental method using four groups; three experimental groups and one fixed. The first group uses training with weights, the second group uses plyometric training, the third group uses the combined (with weights and plyometric) and the fourth uses usual traditional training. The experimental work took place for three months Research methods. Scientific-methodical and special literature analysis, testing, pedagogical experiment, methods of mathematical statistics. Results. The results showed progress in the experimental groups, in particular the mixed application group (weightlifting and plyometric). The effectiveness of the development of certain physical qualities and the extended shooting of handball players (13-15 years-male)showed it vividly.